Cytotoxic chemotherapy - Sawyer, Michael (Henry Stewart Talks, 2009)
Alkylating agents, Nitrogen mustards, Nucleotide excision repair, Mismatch repair, Platinum compounds, Tubulin acting agents, Tubulin/microtubule structure and function, Vinca alkaloids, Antimetabolites, Anthracyclines, Nucleoside transporters, Topisomerase inhibitors